Profile of the practice of self-medication in children aged 0 to 14 years in the city of Manaus (Research, Society and Development, 2023)
Introduction: Self-medication can be defined as the use of medication on your own to treat pathologies. The misuse of medicines can cause damage to the healthy balance of the human body, not least because medicines used without guidance can camouflage certain pathologies, making their treatment even more difficult. Objective: To evaluate the profile of self-medication in children aged 0-14 years in the city of Manaus - Amazonas. Methodology: This is a quantitative research. Results: The frequency of self-medication among the interviewed parents was 90%. The most cited influencing factors of self-medication were: informal guidance from a health professional (31.06%); Indication of friends and family (20.45%) and Own knowledge (20.45%). The main groups of drugs used in self-medication were: analgesics and antipyretics (51.06%) and anti-inflammatories (12.77%). The clinical situations in which the practice of self-medication occurred the most were: flu and colds (30.77%); fever (26.28%) and pain (19.87%). Conclusion: Self-medication in children up to 14 years of age is often practiced on a daily basis and usually takes place under the responsibility of parents and/or guardians, most of the time, in situations of flu/cold and fever, either by guidance of a health professional or personal knowledge. The reduction of this practice should be encouraged, through the mobilization of the rational use of medicines and assistance in the safe administration of drugs in children.